2012
DOI: 10.5296/ijl.v4i4.2459
|View full text |Cite
|
Sign up to set email alerts
|

EAP Students’ Reading Motivation of English Academic Expository Texts: A Mixed Methods Design

Abstract: This mixed methods research study explored the nature of reading motivation of selected EAP students majoring in medicine at an Iranian Medical University. In addition, this study examined the relationships between reading motivation constructs and reading proficiency (RP). In the quantitative part of the study, 95 students responded to the adapted version of the Reading Motivation Questionnaire (RMQ). In the qualitative part of the study, eight students (4 high and 4 low achievers) participated in semi-struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…They were unhappy with other parties, such as the teacher educators' ways of teaching, the learning activities, and/or the reading materials. They did not have awareness that reading academic materials is a compulsory activity to uptake knowledge in higher education level [1] and the key to academic life success [4,[6][7][8][9]. Sadly, none of the EFL student teachers exhibited positive emotional reactions towards course reading, which was an unavoidable activity during their study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They were unhappy with other parties, such as the teacher educators' ways of teaching, the learning activities, and/or the reading materials. They did not have awareness that reading academic materials is a compulsory activity to uptake knowledge in higher education level [1] and the key to academic life success [4,[6][7][8][9]. Sadly, none of the EFL student teachers exhibited positive emotional reactions towards course reading, which was an unavoidable activity during their study.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, they are expected to make an analysis and synthesis of texts with varying levels of difficulties [4,5]. Therefore, to succeed academically, English reading skills should be fostered so that students can develop personally and hence succeed academically [4,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact motivated learners had more eagerness for reading texts. There was little research that studied the connection between motivation and reading comprehension (Jafari & Shokrpour, 2012).…”
Section: Email: Info@ijreeonlinecommentioning
confidence: 99%
“…The connection between motivation and reading comprehension has been investigated by a body of research (Jafari & Shokrpour, 2012;Schaffner & Ulferts, 2013;Mermelstein, 2014). In the study conducted by (Jafari & Shokrpour, 2012) that aimed to investigate the relationship between motivation and reading comprehension, the findings indicated that there was a significant correlation between intrinsic motivation and learners reading development. In fact motivated learners had more eagerness for reading texts.…”
Section: Introductionmentioning
confidence: 99%